(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The article is devoted to the analysis of approaches to the definition of ‘training’, which is defined as an activity, a stock of knowledge and readiness. The article also analyses the interpretation of ‘professional training’ by different scholars. In various scientific sources, vocational training is seen as a multidimensional phenomenon that combines the processes of learning, readiness and development of key competencies necessary for performing professional tasks. This paper explores the interpretation of the concept of ‘vocational training’ in pedagogical, psychological, sociological, economic, technological and cultural aspects. In our scientific research, we analysed modern approaches to the formation of professional readiness of logisticians, in particular, the definition of communication, socio-cultural, professional, managerial, technological, creative and ethical competences. The approaches to the interpretation of the professional training of future logistics specialists, in particular its definition in the context of the formation of competencies necessary for the performance of logistics functions, are analysed. The key components of professional training, such as the formation of specialised knowledge, practical skills, socio-cultural and technological competencies, as well as professional responsibility, are identified. The results of the study indicate the need to integrate interdisciplinary approaches to professional training, which will ensure high-quality training of specialists for modern challenges in the field of logistics.